Canva-Based E-Modules And Test Forms For Enchancing Critical Thinking Abilities In Class VIII Students - Ni Putu Widya Purnamawati; I Made Sugiarta; Ni Made Sri Mertasari (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the low mathematical critical thinking abilities of students because they still face difficulties in solving mathematical problems, especially those requiring analytical and problem-solving skills. The objective of this study is to determine the influence of Canva-based e-module and the form of tests on the critical thinking abilities of eighth-grade students at SMP Negeri 3 Mengwi. This research is a quasi-experimental study with a 2x2 factorial design. The study population includes all eighth-grade students, comprising 11 classes. The research sample was selected through random sampling, resulting in 4 classes as the research sample. Data collection involved critical thinking ability data through performance tests and essay tests. The results of the research indicate that, first, the two-way ANOVA calculations show a significance value of 0.000 at a significance level of 0.05. This implies a difference in critical thinking abilities between students using Canva-based e-modules and those using textbooks. Second, the two-way ANOVA calculations show a significance value of 0.009 at a significance level of 0.05. This implies a difference in critical thinking abilities between students given performance tests and those given essay tests. Third, there is an interaction effect between teaching materials and the form of tests on critical thinking abilities. The analysis results indicate interaction, which is further examined through Scheffe's test. The implications of this research are that the use of Canva-based e-modules and performance-based tests is effective in enhancing and evaluating critical thinking abilities.